2018
DOI: 10.1038/s41394-018-0049-8
|View full text |Cite
|
Sign up to set email alerts
|

Spinal cord injury epidemiological profile in the Sarah Network of Rehabilitation Hospitals—a Brazilian population sample

Abstract: Gunshot wounds were the main cause of SCI in our population, comprising mostly male individuals with thoracic injury, resulting in complete SCI. Data show a high incidence of SCI in young adults owing to violence in Brazil.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
11
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 13 publications
3
11
0
3
Order By: Relevance
“…We found that falls (both from a small and large height) and MVCs were the main causes of SCIs and occurred in nearly all age groups. The incidence of violence also varied by country and region, with the incidence of SCI due to violence being as low as 0.40% in Beijing [6] and as high as 28.4% in Brazil [20]. In the same fashion, gunshot wounds were rare in China, mainly due to the strict social security and gun control implemented by the state.…”
Section: Discussionmentioning
confidence: 99%
“…We found that falls (both from a small and large height) and MVCs were the main causes of SCIs and occurred in nearly all age groups. The incidence of violence also varied by country and region, with the incidence of SCI due to violence being as low as 0.40% in Beijing [6] and as high as 28.4% in Brazil [20]. In the same fashion, gunshot wounds were rare in China, mainly due to the strict social security and gun control implemented by the state.…”
Section: Discussionmentioning
confidence: 99%
“…in Brazil [20]. In the same fashion, gunshot wounds were rare in China, mainly due to the strict social security and gun control implemented by the state.…”
Section: Discussionmentioning
confidence: 96%
“…This rate varies from one country to another, dropping down to 8.4% in Thailand and as low as 1.9% in Turkey. [5][6][7] In the US, 12.2% (784 out of a total of 17,730 new annual SCIs) are secondary to gunshot injuries. 8,9 Spinal cord injuries also result in a significant health and financial burden at the level of the individual patient and their families, as well as at the level of the healthcare system.…”
Section: Discussionmentioning
confidence: 99%